Case report: catamenial hyperglycemia: the trigger of recurrent DKA in a female patient with three-year follow-up - Cholekho, Sumita; Fan, Zuli; Tan, Huiwen (Frontiers in Endocrinology, 2024)
Abstract Background: Catamenial hyperglycemia is a rare type of spontaneous, recurring Diabetic Ketoacidosis( DKA) in females during the luteal phase, most commonly observed in type 1 diabetes mellitus. Even with controlled serum glucose levels, adherence to a diabetic diet, medications, and in the absence of other common influencing factors such as infection, glucose levels tend to increase during the premenstrual period. This uncommon issue related to the menstrual cycle phase has not been extensively researched. Therefore, this study aims to diagnose catamenial hyperglycemia promptly and initiate early treatment to prevent complications. Case report: We presented a case of a 19-year-old girl who experienced recurrent DKA during the premenstrual period, without an apparent cause. She was admitted multiple times to various hospitals and sought consultations, undergoing numerous laboratory and imaging examinations, yet the etiology remained elusive. Ultimately, she received a diagnosis of catamenial diabetic hyperglycemia . To prevent recurrence of complications associated with catamenial hyperglycemia, we initiated a comprehensive approach which included continuous glucose monitoring, adherence to a strict diabetic diet, diabetic health education, regular exercise, timely medication administration, and increase in insulin dosage during the premenstrual period based on glucose levels. Conclusions: Although catamenial hyperglycemia is rare, it should be considered a cause of recurrent hyperglycemia in any postpubertal female to prevent complications. The specific underlying mechanisms responsible for catamenial hyperglycemia or DKA remain unidentified.